Acorus calamus var. angustatus Besser: Insight into current research on ethnopharmacological use, phytochemistry, pharmacology, toxicology, and pharmacokinetics. (June 2023) - He, Xirui; Chen, Xufei; Yang, Yan; Liu, Yujie; Xie, Yulu
Abstract: A. calamus var. angustatus Besser is an important traditional medicinal herb commonly used in China and other Asian countries. This study is the first systematic review of the literature to thoroughly analyze the ethnopharmacological application, phytochemistry, pharmacology, toxicology and pharmacokinetic properties of A. calamus var. angustatus Besser and provides a rationale for future research and prospects for application in clinical treatment. Information on relevant studies investigating A. calamus var. angustatus Besser was collected from SciFinder, the Web of Science, PubMed, CNKI, Elsevier, ResearchGate, ACS, Flora of China, and Baidu Scholar, etc. up to December 2022. In addition, information was also obtained from Pharmacopeias, books on Chinese herbal classics, local books, as well as PhD and MS dissertations. A. calamus var. angustatus Besser has played an important role in the herbal treatment of coma, convulsion, amnesia, and dementia for thousands of years. Studies investigating the chemical constituents of A. calamus var. angustatus Besser have isolated and identified 234 small-molecule compounds and a few polysaccharides. Among them, simple phenylpropanoids represented by asarone analogues and lignans are the two main active ingredients, which can be considered characteristic chemotaxonomic markers of this herb. In vitro and in vivo pharmacological studies indicated that crude extracts and active compounds from A. calamus var. angustatus Besser display a wide range of pharmacological activities, especially as treatment for Alzheimer's disease (AD), and anticonvulsant, antidepressant-like, anxiolytic-like, anti-fatigue, anti-Parkinson, neuroprotection, and brain protection properties, providing more evidence to explain the traditional medicinal uses and ethnopharmacology. The clinical therapeutic dose of A. calamus var. angustatus Besser does not present any toxic effects, but its main active ingredients α-asarone and β-asarone at excessive dose may lead to toxicity, and in particular, their respective epoxide metabolites may exert potential toxicity to the liver. This review provides a reference and further information for the future development and clinical application of A. calamus var. angustatus Besser. Graphical abstract: Image 1 Highlights: Overview of potential therapeutics from A. calamus var. angustatus Besser. Over 234 naturally compounds from A. calamus var. angustatus Besser are reported. Asarone analogues are the active ingredients in A. calamus var. angustatus Besser. Benefit for future development and utilization of A. calamus var. angustatus Besser.